A shield in battle: the contingent value of human rights treaties to INGOs in autocracies. Issue 4 (21st April 2019) - Stobb, Maureen
ABSTRACT: Human rights treaties make a difference under certain circumstances. Advocates find them useful in their work. In autocracies, where the ground is less fertile, human rights agreements can be particularly valuable. I contend that the impact of ratification depends on the type of advocacy organisations present in the autocracy. My theory points to the importance of INGOs expressing a commitment to international values by obtaining consultative status with the United Nations Economic, Social and Cultural Council. I expect that human rights treaties will be a more profitable resource for these advocates in a repressive environment, serving as a shield in a high stakes battle. My primary findings support my expectations. However, the results are not robust to different model specifications. I conclude that distinctions among INGO types have important implications for the impact of treaty ratification, but the consequences may not be what one would expect, and may depend on the form of abuse analysed.